Pseudothrombocytopenia induced by incubation at 37 ℃ in ethylenediaminetetraacetic acid tubes - Zhang, Lixia; Wang, Lin; Gao, Li; Xu, Jian; Pan, Shiyang (Journal of Laboratory and Precision Medicine, 2017)
Ethylenediaminetetraacetic acid (EDTA) is the anticoagulant currently used for cell blood counts. Several studies showed that exposure of platelets (PLTs) to EDTA for a short period of time promote tyrosine phosphorylation of certain proteins, events that are related to activation. Spuriously low PLT counts were observed in a patient with cold agglutinins after the blood being warmed at 37 ℃ in EDTA tubes. Some cloudy polymers were found on peripheral blood smear after incubation at 37 ℃ for 15 minutes. These data suggest that PLT were activated after being warmed to 37 ℃ with EDTA. This process initiated coagulation and generated fibrin and PLT polymers from PLT agglutination and release. This case report hence describes a very rare phenomenon, which produces a spuriously low PLT counts caused by warming of EDTA tubes at 37 ℃.